Binuclear Metal Chelates of 1,2,5,6-tetraphenyl-3,4-diaza- 1,6 Dihydroxyimino-2,4-hexadiene with Ni(II), Co(II), Mn(II) and Cu(II) - Sahu, K. (Asian Journal of Chemistry, 2010)
Binuclear metal chelates of 1,2,5,6-tetraphenyl-3,4-diaza-1,6-dihydroxyimino-2,4-hexadiene with Ni(II}, Co(II), Mn(II) and Cu(II) of the type M2L2·XH2O have been synthesised. IR spectra show coordination of the ligand with the metal ions through azomethine nitrogen atoms in a bi-bidentate manner. Electronic spectra and magnetic moment suggest dinuclear square planar structure about the metal ion.